Gerakan Scaling-up Nutrition (SUN): Meningkatkan Kerjasama Kemitraan Multi Stakholder dalam Mengatasi Tantangan Kekurangan Zat Gizi di Indonesia - Puspo Edi Giriwono; Stefanus Indrayana (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Average protein intake of Indonesian is relatively low. Black bean (Phaeseolus vulgaris) is one of the Indonesia local pulses containing high content of protein (16.6% wet basis). Black bean our has a potential as a substitute for wheat our in bakery products such as brownies. The objective of this research was to determine suitable milling procedure of black bean and to evaluate black bean our substitution on physical, chemical, and sensory effects of of brownies. Two different milling methods (dry and wet milling) were studied to produce black bean our after different soaking times (6, 12, and 18 hours). Dry milling method was optimum after 12 hours of soaking. Black bean our contained 23.9% of protein, 62.61% of carbohydrate. The yield of milling process was 49.39% and the our whiteness was 57.74. Substitution 25% of black bean our in brownies making did not decrease brownies characteristics. The brownies had 7.8% of protein content, 513.13 gram force of hardness, 0.71 of elasticity, 0.36 of cohesiveness, with acceptable sensory qualities. Addressing malnutrition in the global scale requires intiatives beginning from every individual country level. This approach in alleviating national nutritional issues at the domestic population contributes signi cantly to the overall worldwide mission to eradicate malnutrition and its detrimental effects which has been outlined in the Millenium Development Goals (MDG) established at the turn of the century. Overcoming issues in nutrient de ciencies becomes the responsibility of all stakeholders, government, industry, academic and other organizations, and include most important of all, the general public. In this integrated approach, an initiative known as the Scaling-Up Nutrition movement is gaining wide recognition and momentum in addressing nutritional problems the world faces. One course of action that may be “scaled-up” involving all parties, is forti cation of food products as an ef cient and effective effort to alleviate nutritional de ciencies, more often than not, de ciencies in micronutrients. Some challenges are expected in this avenue, such as sustainable support for forti cation programs in the form of multi-stakeholder partnerships, effecting policy change to support mandatory forti cation, long- term monitoring of the programs’ compliance and ef cacy in light of limited resources, and increasing awareness and uptake of forti ed products through social marketing campaigns. Thus what is required is the development of terms of governance and agreement for multi-stakeholder partnerships, supporting sustainable business model and its monitoring, for effectiveness and for enforcement of fortification legislation.